APLIKASI MOBILE BROADCAST INFORMASI PERKULIAHAN BERBASIS ANDROID - Azlin Azlin; La Atina La Atina; Ria Indrasari (Prodi Teknik Informatika Unidayan Baubau, 2022)
Many lecture activities on campus, such as class schedules, still use the manual method to trigger them for students. This causes that the information provided is often not delivered as a result of time constraints, so manual notification is not very helpful. The media used in the informatics engineering study program to convey current information are bulletin boards and the campus' official portal website. Therefore we need a system that can convey lecture information directly to students. This study aims to build a Mobile Broadcast Application for Disseminating Lecture Information for students. The research methodology used in this research is using the waterfall model. The waterfall model provides a sequential software life-flow approach starting from analysis, design, coding, and testing. Analysis is a stage that is used to analyze the specifications or requirements for the application to be built. This research produced a Mobile Broadcast Application for Information Dissemination of Android-Based Lectures for the Informatics Engineering Study Program which makes it easier for students to obtain lecture information.